Faktor-faktor Eksternal Minat Berwirausaha - Siregar, Silvia; Sofyan, Herminarto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This research aims to analyze the influence of Digital Literacy, Social Media, Entrepreneurship Education, and vocational skills on entrepreneurial interest among vocational high school students in the fashion design program in Sleman Regency. This study employs a quantitative approach with an ex-post facto design. The sampling technique used cluster sampling, followed by proportionate random sampling from each vocational school, resulting in a sample of 161 XII students from the Fashion Design Program. Data were collected using Google Form questionnaires that had been tested for validity and reliability, and data analysis was conducted using regression analysis. The results of this study are as follows: (1) Digital literacy has a positive and significant effect on entrepreneurial interest; (2) Social media has a positive and significant effect on entrepreneurial interest; (3) Entrepreneurship education has a positive and significant effect on entrepreneurial interest; (4) Vocational skills do not significantly affect entrepreneurial interest; (5) Digital literacy, social media, entrepreneurship education, and vocational skills collectively have a positive and significant effect on entrepreneurial interest. This research can provide insights for determining entrepreneurship education strategies to meet the demands and needs of the dynamic business and industrial world.